2016
DOI: 10.1007/978-1-4939-3995-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Does a Self-Similarity Logic Shape the Organization of the Nervous System?

Abstract: From the morphological point of view, the nervous system exhibits a fractal, self-similar geometry at various levels of observations, from single cells up\ud to cell networks. From the functional point of view, it is characterized by a hierarchic organization in which self-similar structures (networks) of different miniaturizations\ud are nested within each other. In particular, neuronal networks, interconnected to form neuronal systems, are formed by neurons, which operate thanks to their\ud molecular network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…A hierarchical or nested architecture has been suggested as a suitable model providing a unified view of the different spatial scales characterizing the brain network organization (Sporns et al, 2005;Sporns, 2013;Guidolin et al, 2016). In this respect, an almost general consensus exists (see Sporns et al, 2005;Sporns, 2013) in targeting at least three levels of organization: the macroscale of brain areas and regions, the mesoscale involving nerve cells networks, and the microscale where single cells and synaptic clusters (Cutsuridis et al, 2009) can be found.…”
Section: Discussionmentioning
confidence: 99%
“…A hierarchical or nested architecture has been suggested as a suitable model providing a unified view of the different spatial scales characterizing the brain network organization (Sporns et al, 2005;Sporns, 2013;Guidolin et al, 2016). In this respect, an almost general consensus exists (see Sporns et al, 2005;Sporns, 2013) in targeting at least three levels of organization: the macroscale of brain areas and regions, the mesoscale involving nerve cells networks, and the microscale where single cells and synaptic clusters (Cutsuridis et al, 2009) can be found.…”
Section: Discussionmentioning
confidence: 99%
“…A network may be realized physically in space, and may be geometrically self-similar, but this does not necessarily imply that it is a scale-free “network.” In the brain, e.g. we can see a geometrically self-similar structure from the micro-level up to the complex cellular networks connecting different areas ( Guidolin et al. 2016 ), but the network (graph) itself is not scale-free.…”
Section: Scale-free Systems In General and In Naturementioning
confidence: 99%
“…From a geometric perspective, complex networks on the macro-scale show high resemblance to micro-scale neuronal connections ( Guidolin et al. 2016 ).…”
Section: Scale-free Structure In the Brain At Different Levels Of Org...mentioning
confidence: 99%
“…This effect is typical in genomics, but it is also common in the theory of nonlinear dynamical systems, signal processing, brain tissue morphology, etc. [52]–[59].…”
Section: Resultsmentioning
confidence: 99%
“…The large-size genomic data are often patterned, and each pattern can have its fractal dimension, i.e., the sequences can be multifractals [31]. This effect is typical in genomics, but it is also common in the theory of nonlinear dynamical systems, signal processing and brain tissue morphology, among others [51]-[63].…”
Section: Methodsmentioning
confidence: 99%